Patrilineal Constraints and Female Creativity: Case on Gitar Tunggal Lampung - Hidayatullah, Riyan; Arkhasa Nikko Mazlan, Chamil (Gondang: Jurnal Seni dan Budaya, 2024)
Women have played a significant role in the history of Lampung's indigenous people, a.k.a Ulun Lappung. Lampung and women have had a long relationship since the Lampung people's ancestors settled in this area in the 14th century. Ratu Sekarmong, a Lampung indigenous resident, has led the Tumi tribe in Sekala Brak. Then women played a unique role in the stringed music of the Pepadun community two generations ago, particularly the gitar tunggal. Participant observations of female gitar tunggal performers, particularly those from the Pepadun ethnic group of Lampung, were used to conduct this qualitative study. The number of female guitar players in Lampung is currently dispersed. Women of the ethnic Pepadun make up the majority of the performers. In-depth descriptions are also produced using ethnographic data and digital documents from the internet. Investigations on virtual field sites, interviews, and literature reviews are used to collect research data. According to the findings, male and female gitar tunggal performers use the same way in techniques. Contrarily, female guitarists have different goals than male guitarists. Women are prohibited from playing stringed instruments in public or in the local music industry. In addition, male performers typically remain active on stage, whereas female performers only reside in their homes. In the traditional view, their creativity is only used for household amusement. As a result, female guitarists must advance new coping mechanisms that affect their ability to retain music. Women's contributions to developing Lampung stringed music must be acknowledged, particularly in light of the patrilineal Lampung traditional system.